2021
DOI: 10.1111/gcb.15783
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability and origin of CO2 and CH4 tree stem fluxes in an upland forest

Abstract: The exchange of multiple greenhouse gases (i.e., CO2 and CH4) between tree stems and the atmosphere represents a knowledge gap in the global carbon cycle. Stem CO2 and CH4 fluxes vary across time and space and are unclear, which are their individual or shared drivers. Here we measured CO2 and CH4 fluxes at different stem heights combining manual (biweekly; n = 678) and automated (hourly; n > 38,000) measurements in a temperate upland forest. All trees showed CO2 and CH4 emissions despite 20% of measurements sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Several previous studies have also indicated that methanogens are present within poplar trees (such as P. alba, P. deltoides, and P. angustifolia) and promote generating CH 4 (Zeikus & Ward, 1974;Yip et al, 2019;Flanagan et al, 2021). Barba et al (2021) recently postulated that stem CH 4 flux in upland trees is likely due to the production in situ through comparing manual and automated measurements, laboratory incubations, and stem CH 4 concentrations. However, we found the stem CH 4 emissions to occur over the entire measurement period (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several previous studies have also indicated that methanogens are present within poplar trees (such as P. alba, P. deltoides, and P. angustifolia) and promote generating CH 4 (Zeikus & Ward, 1974;Yip et al, 2019;Flanagan et al, 2021). Barba et al (2021) recently postulated that stem CH 4 flux in upland trees is likely due to the production in situ through comparing manual and automated measurements, laboratory incubations, and stem CH 4 concentrations. However, we found the stem CH 4 emissions to occur over the entire measurement period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Barba et al . (2021) recently postulated that stem CH 4 flux in upland trees is likely due to the production in situ through comparing manual and automated measurements, laboratory incubations, and stem CH 4 concentrations. However, we found the stem CH 4 emissions to occur over the entire measurement period (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, fluxes of GPP and Reco are estimated as a result of a model based on temperature or light (Lasslop et al., 2012; Reichstein et al., 2005), and are not directly measured which introduces additional uncertainties. While both chambers and EC based approaches have their own benefits and limitations, the paired use of methods can be an especially powerful tool for reconciling differences between approaches (Barba et al., 2021; Fox et al., 2008). Specifically, including a data subset with higher spatiotemporal integration from EC (i.e., daily averaged data) can serve as a target benchmark to compare other methods, thus helping to bridge the gap between different measurement scales (e.g., plot‐ecosystem) (Hill, Barba, et al., 2021; Lucas‐Moffat et al., 2018).…”
Section: Introductionmentioning
confidence: 99%